2017
DOI: 10.1016/j.gaceta.2016.06.014
|View full text |Cite|
|
Sign up to set email alerts
|

Indicadores contextuales para evaluar los determinantes sociales de la salud y la crisis económica española

Abstract: We have provided an extensive directory of contextual indicators on social determinants of health and a database to facilitate assessment of the impact of the economic recession on health and health inequalities in Spain and its autonomous regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…The Health Care and Social Survey (ESSOC, Encuesta Sanitaria y SOCial) research project arises from the need to provide specific, reliable, early, and timely data on the impact of COVID-19, which can then be considered when making decisions to prepare and provide an effective Public Health response in the different populations affected, especially the most vulnerable such as, among others, the elderly, the chronically ill, or those at risk of exclusion. ESSOC focuses on Public Health [50] and relies on the participation of society to obtain information on people's health and their quality of life in order to be able to intervene both individually and collectively in the face of the pandemic (Table 1). The research project is based on a real-world data [51] design that integrates observational data extracted from multiple sources of differing natures and perspectives, i.e., both probabilistic and administrative.…”
Section: The Essoc Study Frameworkmentioning
confidence: 99%
“…The Health Care and Social Survey (ESSOC, Encuesta Sanitaria y SOCial) research project arises from the need to provide specific, reliable, early, and timely data on the impact of COVID-19, which can then be considered when making decisions to prepare and provide an effective Public Health response in the different populations affected, especially the most vulnerable such as, among others, the elderly, the chronically ill, or those at risk of exclusion. ESSOC focuses on Public Health [50] and relies on the participation of society to obtain information on people's health and their quality of life in order to be able to intervene both individually and collectively in the face of the pandemic (Table 1). The research project is based on a real-world data [51] design that integrates observational data extracted from multiple sources of differing natures and perspectives, i.e., both probabilistic and administrative.…”
Section: The Essoc Study Frameworkmentioning
confidence: 99%
“…La disponibilidad de fuentes adecuadas sobre los factores causales y sobre los indicadores de salud de la población en el espacio es clave para poder realizar las investigaciones más concisas posibles sobre los aspectos de Geografía de la Salud que se deseen analizar (Olivera, 1993;Cabrera-León et al, 2017). Asimismo, para estudiar las relaciones entre las variables territoriales y los indicadores de salud se han de emplear adecuados métodos geoestadísticos, entre los que destacan métodos de regresión ecológica, de correlación espacial y de interpolación espacial (Buzai, 2007(Buzai, , 2015Borrell et al, 2010;Aránguez, Arribas, Aránguez y Ordóñez, 2012).…”
Section: Bases Para Los Estudios De Geografía De La Saludunclassified
“…In this regard, with regard to the extent of social and economic vulnerability in the field of health, a study by Stuckler et al [6,7] in post-communist countries found that massive privatization programs in the health system increased short-term adult male mortality rates by 12.8% among the most disadvantaged social classes. On a national level, the impact of austerity policies on the health of the Spanish population has been the subject of numerous investigations from the public health field, concluding that the effects on the population are heterogeneous and controversial, endangering the sustainability of the national health system [8][9][10][11][12]. In particular, important differences have been identified between the Autonomous Communities in terms of the management of the economic crisis and austerity policies.…”
Section: Introductionmentioning
confidence: 99%
“…While the government of the Basque Country did not implement austerity policies during the crisis, in La Rioja, Madrid and the Balearic Islands, privatization policies were implemented in the health system [8]. In addition, the study conducted by Del Pozo-Rubio et al [10] showed how the co-payment of dependency introduced in Spain through the Resolution of 13 July 2012 meant, on the one hand, an unequal application of co-payments between the Autonomous Communities, with Andalusia, Valencia and Catalonia having the highest levels of co-payment, and, on the other hand, how the co-payment went from 20% in the national average before the reform to 53.54% after the reform. Thus, these studies would confirm both the inequalities between social classes and between the different regions of Spain.…”
Section: Introductionmentioning
confidence: 99%